Advances in Perovskite-Based Solar Cells (Journal of Informatics and Mathematical Sciences, 2017)
The increase in energy demand due to increase in population and reduction of fossil fuels has led to the search of alternative energy sources. Solar energy, which is an alternative source of energy, has been in the fore front of this research. Various methods of converting solar energy into electricity has been attained by silicon solar cells, thin film solar cells, dye sensitized solar cells and perovskite solar cells. Unlike dye sensitized solar cells, perovskite solar cells based on lead halide perovskite or organic-inorganic halide perovskite have had a significant impact on photovoltaic devices. A power conversion efficiency of approximately 20.1% has been attained by perovskite solar cells compared to organic solar cells. Also, several fabrication techniques, hole and electron transport materials have been developed for high performance. Although, some issues need to be addressed before commercialization is possible. Issues like stability of the cells under moisture and temperature. In this review, fundamental aspects of the perovskite device and recent breakthroughs are illustrated.
Keywords: Hole transport material; Electron transport material; Perovskite; Stability